“SILAHTURAHMI WONG PINGGIRAN” - Daniel Ortega Galed (Studia Philosophica et Theologica, 2015)
What we know about our daily living together is that we just live our business of working together. But, what we might not know about our living together is that it contains beautiful tradition, the so-called “Silaturahmi”. We are probably familiar with the terminology, but there must be something profound in there. Based on this, I would like to present my research on the theme of “Silaturahmi” not from Experts’ perspective but from “wong pinggiran” (ordinary people living in perifery of Malang). Research is applying phenomenological methodology, that is, researcher (myself) go to the subjects and listen to them attentively. What I discover is indeed an “authentic” voice of peace.